ESTABLISHMENT OF DRAFT AGREEMENT/WORK CONTRACT FOR SCRAP SMES (WAREHOUSE PARDEDE) - Tomi Suhendra Pardede; Agustianto Agustianto (Universitas Internasional Batam, 2022)
Scrap (Gudang Pardede) is a business engaged in collecting used goods which will then be sold to recipient companies, but the author's focus on this service is on partner businesses in other fields, namely oil palm agriculture. The background of the problems faced by partners is an alleged unlawful act committed by their workers, in the form of embezzlement of harvest money, and others that result in losses to partners, where from the harvest the partners do not get the slightest result or profit, while the land is partner's. So the author believes that the work agreement is an alternative solution that partners can use to deal with problems like this, and of course also useful for partners in the future. The expected outputs from this community service activity are community service reports, service articles and draft work agreements. In this community service activity, the implementation method consists of four stages. The first stage is preparation where the researcher will conduct observations and interviews. The second stage is implementation where researchers will go directly to the field to carry out service activities. The third stage is assessment, and the fourth stage is reporting.